Semantic Web Technology and Recommender Systems - Kotis, Konstantinos; Spiliotopoulos, Dimitris (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this book (Volume I), 13 papers have been published on different topics of the wide research areas of Semantic Web and Recommender systems. These papers have been carefully selected based on the peer review of several respectful reviewers organized by MDPI's BDCC journal. This issue has attracted well-known international research teams, who we would like to thank for their work.